Arterial fluid flow investigation on double stenoses contact morphology for medical application - Nor Shakirina Nadzri (School of Microelectronic Engineering, Universiti Malaysia Perlis, 2015)
The main interest of this research is to investigate the fluid flow characteristics across a couple of stenoses in a coronary artery using simulation method.